2016
DOI: 10.1111/jre.12411
|View full text |Cite
|
Sign up to set email alerts
|

Black tea theaflavins attenuate Porphyromonas gingivalis virulence properties, modulate gingival keratinocyte tight junction integrity and exert anti‐inflammatory activity

Abstract: This study provides clear evidence that black tea TFs represent promising multifunctional therapeutic agents for prevention and treatment of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…In addition, TFs can attenuate the secretion of IL‐8 in oral epithelial cells after stimulation with LPS by inhibiting activation of the IkappaB kinase and activator protein‐1 pathways . Recently, Ben Lagha and Grenier reported that TFs can inhibit IL‐6, IL‐8, and MMP‐9 secretion from P. gingivalis ‐stimulated macrophages, mostly likely by blocking activation of the NF‐κB signaling pathway. These data indicate that TFs may play a significant role in antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, TFs can attenuate the secretion of IL‐8 in oral epithelial cells after stimulation with LPS by inhibiting activation of the IkappaB kinase and activator protein‐1 pathways . Recently, Ben Lagha and Grenier reported that TFs can inhibit IL‐6, IL‐8, and MMP‐9 secretion from P. gingivalis ‐stimulated macrophages, mostly likely by blocking activation of the NF‐κB signaling pathway. These data indicate that TFs may play a significant role in antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TF‐3 inhibited tumor necrosis factor receptor superfamily 14‐induced IL‐6 production in human gingival fibroblasts . Recently, it was reported that TFs attenuated the secretion of IL‐6, chemokine ligand 8 (CXCL‐8 or IL‐8), and MMP‐9 in macrophages stimulated by Porphyromonas gingivalis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of resveratrol on the adherence of P. gingivalis to Matrigel™ (BD Biosciences, San Jose, CA, USA), a basement membrane matrix model composed of several extracellular matrix proteins, including laminin, type IV collagen, heparin sulfate proteoglycans, and entactin, was evaluated. Porphyromonas gingivalis cells were first labeled with fluorescein isothiocyanate (FITC) as described in a previous study (Ben Lagha & Grenier, ). FITC‐labeled bacteria were suspended in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…After 24 hr, the cells were collected by centrifugation and were lysed. mRNA was purified using an RNeasy plus minikit (Qiagen Canada Inc., Toronto, ON, Canada) and was reverse‐transcribed into cDNA before performing a quantitative real‐time PCR analysis to quantify TREM‐1 and DAP12 mRNA expression as described in a previous study (Ben Lagha & Grenier, ). The GAPDH rRNA gene was used as an internal control for data normalization.…”
Section: Methodsmentioning
confidence: 99%